SYSTEM ADMINISTRATION EQUIPMENT RENTAL MUSIC AND SOUND SYSTEM IN MUSIC STUDIO 48 WITH MICROSOFT VISUAL BASIC 6.0 - Annisa Dwi Holy (Jurnal Sistem Informasi, 2009)
Rental of musical instruments and sound systems at 48 is still MUSIC STUDIO done manually, so based on the analysis will be needed to  create a computer-based administration system in accordance with needs and desires of the leadership, particularly in terms of equipment leasing, payment receipts, and reports. Analysis performed on 48 MUSIC STUDIO through the documents and interview directly with stakeholders to obtain accurate data. The menu is presented properly designed and adjusted to the leadership desires. Starting from design input to output leasing process so as to form a report in accordance with accounting theory. This strongly supports the readiness of companies in the future when developing and audited by the auditors. Recording process is still done manually, requires a longer time compared to using computer technology.